Crosslinked Hyaluronan Electrospun Nanofibers for Ferulic Acid Ocular Delivery - Maria Aurora Grimaudo; Angel Concheiro; Carmen Alvarez-Lorenzo (MDPI AG, 2020)
Electrospun nanofibers are gaining interest as ocular drug delivery platforms that may adapt to the eye surface and provide sustained release. The aim of this work was to design an innovative ophthalmic insert composed of hyaluronan (HA) nanofibers for the dual delivery of an antioxidant (ferulic acid, FA) and an antimicrobial peptide (ε-polylysine, ε-PL). Polyvinylpyrrolidone (PVP) was added to facilitate the electrospinning process. Fibers with diameters of approx. 100 nm were obtained with PVP 5%-HA 0.8% w/v and PVP 10%-HA 0.5% w/v mixtures in ethanol:water 4:6 v/v. An increase in PVP concentration to 20% w/v in both presence and absence of HA rendered fibers of approx. 1 µm. PVP 5%-HA 0.8% w/v fibers were loaded with 83.3 ± 14.0 µg FA per mg. After nanofibers crosslinking with ε-PL, blank and FA-loaded inserts showed a mean thickness of 270 ± 21 µm and 273 ± 41 µm, respectively. Blank and FA-loaded inserts completely released ε-PL within 30 min under sink conditions, whereas FA-loaded inserts released the antioxidant within 20 min. Both blank and FA-loaded inserts were challenged against Pseudomonas aeruginosa and Staphylococcus aureus, demonstrating their efficacy against relevant microbial species.